Corporate Ratios Predict Banking Operational Trajectories: Rasio Korporasi Memprediksi Lintasan Operasional Perbankan - Eka Oktaviani; Bilgis Nisa’ Intafullaili; Adita Alivia; Rohdotul Mawarda; Misti Hariasih (Proceedings of The ICECRS, 2024)
General Background The banking sector serves as a crucial pillar for national economic stability through targeted funding and lending operations. Specific Background Maintaining robust operational metrics is essential for state-owned institutions like PT Bank Tabungan Negara to sustain public trust and regulatory compliance. Knowledge Gap Despite the widespread application of corporate metrics, existing empirical literature presents contradictory findings regarding how liquidity and debt structures consistently forecast banking success. Aims This research analyzes the predictive role of profit margins, current assets, and debt structures on the corporate financial returns of PT Bank Tabungan Negara from 2021 to 2023. Results Quantitative descriptive analysis reveals that net profit margins progressively grew from 9.21% to 12.37%, demonstrating continuous efficiency. While current asset coverage fluctuated and indicated relatively low short-term fulfillment capacity, the debt-to-equity proportions remained stable. Ultimately, return on assets consistently climbed to 0.79%, confirming that these evaluated metrics significantly forecast institutional trajectories. Novelty This study provides a concentrated longitudinal evaluation of a specific state-owned entity, explicitly linking fluctuating short-term obligations with steady long-term debt and rising asset returns. Implications Institutional management can utilize these specific metric trends to evaluate capital structures, navigate economic challenges, and formulate strategic decisions for future commercial development. Highlights: Net profit margins and return on assets demonstrated continuous upward growth over three consecutive years. Short-term asset coverage experienced significant fluctuations indicating potential vulnerabilities in immediate obligation fulfillments. Debt structures maintained steady stability ensuring consistent long-term institutional funding. Keywords: Profitability Metrics, Current Asset Coverage, Debt Structure, Return On Assets, Financial Evaluation